Neuroprotective Effect of Plasminogen Activator Inhibitor-1 Antagonist in the Rat Model of Mild Traumatic Brain Injury - ERZİK, CAN; AKAKIN, DİLEK; KURTEL, HIZIR; YÜKSEL, MERAL; KOYUNCUOĞLU, TÜRKAN (SPRINGER/PLENUM PUBLISHERS, 2021)
Plasminogen activator inhibitor-1 (PAI-1) antagonists are known for their neuroprotective effects. In this study, it was aimed to investigate the possible protective effects of PAI-1 antagonists in a rat mild traumatic brain injury (TBI) model. Sprague-Dawley male rats were grouped as sham (n = 7), TBI (n = 9), and TBI + PAI-1 antagonist (5 and 10 mg/kg TM5441 and TM5484; n = 6-7). Under anesthesia, TBI was induced by dropping a metal 300-g weight from a height of 1 m on the skull. Before and 24-h after trauma neurological examination, tail suspension, Y-maze, and novel object recognition tests were performed. Twenty-four hours after TBI, the rats were decapitated and activities of myeloperoxidase, nitric oxide release, luminol-, and lucigenin-enhanced chemiluminescence were measured. Also, interleukin-1 beta, interleukin-6, tumor necrosis factor, interleukin-10, tumor growth factor-beta, caspase-3, cleaved caspase-3, and PAI levels were measured with the ELISA method in the brain tissue. Brain injury was graded histopathologically following hematoxylin-eosin staining. Western blot and immunohistochemical investigation for low-density lipoprotein receptor, matrix metalloproteinase-3, and nuclear factor-kappa B were also performed. Data were analyzed using GraphPad Prism 8.0 (GraphPad Software, San Diego, CA, USA) and expressed as means +/- SEM. Values of p < 0.05 were considered to be statistically significant. Higher levels of myeloperoxidase activity in the TBI group (p < 0.05) were found to be suppressed in 5 and 10 mg/kg TM5441 treatment groups (p < 0.05-p < 0.01). The tail suspension test score was increased in the TBI group (p < 0.001) and decreased in all treatment groups (p < 0.05-0.001). The histologic damage score was increased statistically significantly in the cortex, dentate gyrus, and CA3 regions in the TBI group (p < 0.01-0.001), decreased in the treatment groups in the cortex and dentate gyrus (p < 0.05-0.001). PAI antagonists, especially TM5441, have antioxidant and anti-inflammatory properties against mild TBI in the acute period. Behavioral test results were also improved after PAI antagonist treatment after mild TBI.
Keywords: antioxidant; anti-inflammatory; neuroprotection; Plasminogen activator inhibitor-1 antagonist; traumatic brain injury; NF-KAPPA-B; ROLES; THROMBOGENESIS; CONSEQUENCES; PROTEINASE; EXPRESSION; PROTEASE; CLEAVAGE; RELEASE; STROKE